Waqf management for poverty alleviation in Bangladesh towards achieving sustainable development goals - Habibullah, Mohammad; Kassim, Salina; Sharofiddin, Ashurov (ResearchTrentz, 2022)
Bangladesh has a huge amount of waqf assets which can play a very important role to alleviate poverty in Bangladesh and achieving sustainable development goals. The objective of this research is to discover the waqf sectors and opportunities in Bangladesh that can alleviate the poverty with proper utilization and management of these waqf assets by changing the attitude towards the waqf system which can bring results in achieving sustainable development goals for Bangladesh. The qualitative method is applied in this study to evaluate the fundamental concept of waqf from the primary and secondary sources of knowledge in Islam which shows the model of the socio-economic system to alleviate poverty in achieving sustainable development goals (SDGs) in Bangladesh and to identify the challenges of governing the waqf properties accordingly. Thus, this study aims to examine the challenges of governing the waqf and different ways of waqf management to reduce poverty and achieve sustainable development goals in Bangladesh by creating more employment, educating the poor, and facilitating them toward entrepreneurship.